Striated muscle involvement in experimental oral infection by herpes simplex virus type 1 - Gonzalez, Maria Ines (2013)
Herpes simplex virus type 1 is one of the most frequent causes of oral infection in humans, especially during early childhood. Several experimental models have been developed to study the pathogenesis of this virus but all of them employed adult animals. In this work, we developed an experimental model that uses mice younger than 4 days old, to more closely resemble human infection. Mice were infected subcutaneously with the prototype strain McIntyre of Herpes simplex-1, and the progression of infection was studied by immunoperoxidase. All animals died within 24-72 h post-infection, while viral antigens were found in the oral epithelium, nerves and brain. The most striking result was the finding of viral antigens in the nucleus and cytoplasm of cells belonging to striated muscles. Organotypic cultures of striated muscles were performed, and viral replication was observed in them by immunocytochemistry, electron microscopy and viral isolation. We conclude that the infection of striated muscles is present from the onset of oral infection and, eventually, could explain some clinical observations in humans.